Temperature-resistant oil well cement fluid loss agent and preparation method thereof
By using the temperature-resistant oil well cement loss-reducing agent prepared by the vinyl naphthyl silicone polyamine monomer, the problem of degradation of oil well cement loss-reducing agent in the prior art under high temperature conditions and poor dispersion performance is solved, and efficient water loss-reducing and good dispersion performance in high temperature environments is achieved.
Patent Information
- Application Number
- CN202510260340.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-06
AI Technical Summary
The existing oil well cement water loss agent has deteriorated performance and poor dispersion performance under high temperature conditions, making it difficult to meet the needs of deep well and ultra-deep well cementing operations.
A temperature-resistant oil well cement loss-reducing agent is prepared by a specific synthetic method, and a multiple carboxylic acid and sulfonic acid groups are introduced to improve dispersion performance.
It significantly improves the high-temperature resistance and dispersion performance of the water-reducing agent, and can maintain stable performance in high-temperature and high-humidity environments. It is suitable for cementing operations of ordinary formations, salt layers, deep wells and ultra-deep wells.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of well cementing for oil and gas well development, in particular to a temperature-resistant oil well cement fluid loss reducer and a preparation method thereof. Background Art
[0002] In the process of exploration and development of energy resources such as oil and natural gas, oil well cementing operation is a key link to ensure the stability of the well wall and improve the oil and gas recovery rate. However, during the cementing process, the cement slurry often loses water due to the pressure difference, that is, the free water in the cement slurry is filtered out through the permeable formation and enters the formation. This water loss phenomenon will not only reduce the fluidity and thickening time of the cement slurry, but in severe cases, it will even cause the cement slurry to lose its pumping ability, resulting in cementing failure. At the same time, it will also damage the oil and gas layer, which is not conducive to the effective development of oil and gas resources. In order to solve the above problems, the industry widely uses oil well cement fluid loss reducers. The main function of fluid loss reducers is to reduce the water loss of cement slurry, thereby protecting water-sensitive formations, improving cementing operations, ensuring construction safety, and preventing oil and gas layer pollution.
[0003] Traditional oil well cement fluid loss reducers are copolymers made of monomers such as acrylamide, acrylic acid, and 2-acrylamide-2-methylpropane sulfonic acid. However, during cementing operations in deep wells, ultra-deep wells, and wells with abnormal geothermal gradients, these fluid loss reducers will experience hydrolysis or molecular chain breakage as the bottom hole temperature becomes higher and higher (150°C and above), resulting in a significant increase in the water loss of the cement slurry, making it difficult to meet the needs of high-temperature deep well cementing operations. At the same time, due to poor dispersibility, the cement slurry is easily thickened during the cement slurry preparation process, showing strong thixotropy, which is not conducive to on-site construction. Natural polymer modified fluid loss reducers (such as cellulose, starch, lignin, etc.) are disconnected from the polymer side chain substituents under high temperature conditions, and the functional groups are easily detached, resulting in the failure of the fluid loss reducer.
[0004] Patent No. CN100355854C discloses a dispersed fluid loss agent for oilfield cementing and a preparation method thereof, which relates to a dispersed fluid loss agent with high efficiency of fluid loss reduction, low free water and good fluidity, and a wide applicable temperature range (20-120°C) and different types of oil well cements. However, the main body of the fluid loss agent adopts a cross-linked polyvinyl alcohol polymer. Due to the use of polyvinyl alcohol, the fluid loss agent has poor high temperature and salt resistance. Patent No. CN102191027B discloses a high temperature resistant dispersed oil well cement fluid loss agent and a preparation method thereof, which comprises monomers such as 2-acrylamido-2-methylpropanesulfonic acid, N,N-dimethylacrylamide, acrylamide and maleic anhydride. Although the addition of maleic anhydride can further enhance the dispersibility of the fluid loss agent and improve the rheology of cement slurry, it does not solve the problem of easy hydrolysis at high temperature. At the same time, there are problems such as complex preparation process, high cost and limited scope of application.
[0005] In summary, the present invention aims to synthesize a monomer that is resistant to high temperatures and has good dispersibility, and introduce it into a fluid loss reducer to solve the problems of performance degradation and poor dispersibility of oil well cement fluid loss reducers under high temperature conditions in the prior art. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art, provide a temperature-resistant oil well cement fluid loss reducer and a preparation method thereof, and solve the problems of the prior art oil well cement fluid loss reducer having decreased performance and poor dispersion performance under high temperature conditions.
[0007] To achieve the above object, the technical solution adopted by the present invention is: A method for preparing a heat-resistant oil well cement fluid loss reducer is carried out according to the following steps: Step (1), under a nitrogen atmosphere, add vinyl naphthyl organosilicon polyamine monomer and N,N-dimethylformamide to a reaction flask, stir evenly, add 16-bromohexadecanoic acid and triethylamine, stir to react, after the reaction is completed, extract with ethyl acetate and deionized water, concentrate the organic phase, separate by column chromatography (silica gel, 10% methanol in dichloromethane), and obtain vinyl naphthalene organosilicon monomer.
[0008] Step (2), under a nitrogen atmosphere, dissolving 50-65 parts by weight of acrylamide, 10-15 parts of N,N-dimethylacrylamide, 5-8 parts of polyethylene glycol monomethyl ether acrylate and 2-10 parts of alkenylnaphthalene organosilicon monomer in deionized water, adjusting the pH with an aqueous sodium hydroxide solution, introducing nitrogen, heating to 60-80° C., adding dropwise 0.5-0.8 parts of an initiator, continuing the reaction for 2-5 hours, and naturally cooling to room temperature to obtain a temperature-resistant oil well cement fluid loss reducer.
[0009] Preferably, in step (1), the molar ratio of the vinyl naphthyl silicone polyamine monomer, 16-bromohexadecanoic acid, and triethylamine is 1:4.2-5:4.5-6.
[0010] Preferably, in step (1), the reaction temperature is 60-80° C. and the reaction time is 12-24 h.
[0011] Preferably, the initiator in step (2) is any one of ammonium persulfate, benzoyl peroxide or azobisisobutyronitrile.
[0012] Preferably, in step (2), the pH is adjusted to 6-8.
[0013] Preferably, the preparation method of the vinyl naphthyl organosilicon polyamine monomer in step (1) is carried out according to the following steps: Step S1, under a nitrogen atmosphere, add methylvinyldichlorosilane and toluene to a reaction flask, stir evenly, add 6-hydroxy-2-naphthaldehyde and sodium hydride, stir to react, filter after the reaction, wash the organic layer with saturated brine, separate by column chromatography (silica gel, 20% ethyl acetate in n-heptane), and dry to obtain a vinylnaphthyl organosilicon dialdehyde monomer.
[0014] Step S2, under a nitrogen atmosphere, add 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt and methanol to a reaction flask, stir evenly, add vinyl naphthyl organosilicon dialdehyde monomer, stir at 20-35° C. for 2-5 hours, then add sodium cyanoborohydride, react at room temperature for 12-18 hours, filter, concentrate under reduced pressure, separate by column chromatography (silica gel, 5% methanol in dichloromethane), and dry to obtain vinyl naphthyl organosilicon polyamine monomer.
[0015] Preferably, in step S1, the molar ratio of methylvinyldichlorosilane, 6-hydroxy-2-naphthaldehyde and sodium hydride is 1:2.05-2.2:2.3-2.5.
[0016] Preferably, in step S1, the reaction temperature is 90-110° C. and the reaction time is 5-10 h.
[0017] Preferably, in step S2, the molar ratio of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt, vinylnaphthyl organosilicon dialdehyde monomer, and sodium cyanoborohydride is 2.1-2.3:1:2.5-3.5.
[0018] By adopting the above technical solution, the beneficial effects of the present invention are: (1) Excellent high temperature resistance: The naphthalene ring in the fluid loss reducer prepared by the present invention has a stable aromatic ring structure and is not easy to rotate. Its rigid structure can withstand high temperatures without deformation or decomposition, which helps the fluid loss reducer maintain its original performance and form at high temperatures and can significantly improve the thermal stability of the fluid loss reducer. Siloxane has high bond energy and excellent heat resistance, and can maintain stable chemical properties at high temperatures. At the same time, siloxane has the characteristic of not being wetted by water, which helps the fluid loss reducer reduce the influence of water molecules at high temperatures, so that it can still maintain stable performance under high temperature and high humidity environments. The two synergistically play a high temperature resistance role. The multiple carboxylic acid and sulfonic acid groups introduced in the fluid loss reducer are ionized to generate anions such as sulfonate and carboxylate after dissolving in water, which are adsorbed on cement particles through electrostatic action and promote the extension of the polymer chain of the fluid loss reducer. The molecular chain does not break in alkaline cement slurry at high temperatures, and the groups do not fall off, so the fluid loss reducer has excellent high temperature resistance.
[0019] (2) Good dispersibility: The fluid loss reducer prepared by the present invention introduces a plurality of carboxylic acid and sulfonic acid groups. After dissolving in water, it undergoes ionization to generate anions such as sulfonate and carboxylate, which are adsorbed on cement particles through electrostatic action, block the pores of cement particles, make the cement filter cake dense and compact, enhance the binding force between the fluid loss reducer and cement particles, and prevent the agglomeration and sedimentation of cement particles. It helps to form a hydration layer through hydration. When the fluid loss reducer molecules are adsorbed on the surface of cement particles, these hydration layers can reduce the friction between cement particles and further promote the dispersion of cement slurry. At the same time, the polyethylene glycol alkyl and hexadecyl long side chain structures introduced can form an effective steric hindrance in a relatively extended conformation to prevent flocculation and precipitation between cement particles, and form a protective layer of a certain thickness and effective steric hindrance on the surface of cement particles, thereby effectively preventing the close contact and agglomeration of cement particles, so that the cement is highly dispersed.
[0020] (3) Wide scope of application: The fluid loss reducer of the present invention can effectively reduce the water loss of oil well cement slurry while increasing its temperature and salt resistance. It can be used for cementing operations in ordinary formations and salt layers and brine layers, as well as deep wells, ultra-deep wells, and wells with abnormal geothermal gradients. The synthesis method is simple and easy to operate, and the raw materials are reasonably priced and easily available, which is convenient for industrial promotion. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] Unless otherwise specified, the raw materials and reagents used in this application are commercially available or can be prepared by known methods.
[0023] Methylvinyldichlorosilane, CAS number is 124-70-9.
[0024] 6-Hydroxy-2-naphthaldehyde, CAS number is 78119-82-1.
[0025] 2-[(2-Aminoethyl)amino]ethanesulfonic acid sodium salt 34730-59-1.
[0026] 16-Bromohexadecanoic acid, CAS number is 2536-35-8.
[0027] Polyethylene glycol monomethyl ether acrylate, CAS number is 32171-39-4.
[0028] Example 1 (1) Under nitrogen atmosphere, add 30 mmol of methylvinyldichlorosilane and 120 mL of toluene to a reaction flask, stir evenly, then add 63.6 mmol of 6-hydroxy-2-naphthaldehyde and 72 mmol of sodium hydride, react at 100°C for 8 h, filter, wash the organic layer with saturated brine, separate by column chromatography (silica gel, 20% ethyl acetate in n-heptane), and dry to obtain a vinylnaphthyl organosilicon dialdehyde monomer. The preparation reaction formula is as follows:
[0029] (2) Under nitrogen atmosphere, add 55 mmol of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt and 200 mL of methanol to the reaction flask, stir evenly, add 25 mmol of vinyl naphthyl organosilicon dialdehyde monomer, stir at 25°C for 3 h, then add 75 mmol of sodium cyanoborohydride, react at room temperature for 15 h, filter, concentrate under reduced pressure, separate by column chromatography (silica gel, 5% methanol in dichloromethane), and dry to obtain vinyl naphthyl organosilicon polyamine monomer. The preparation reaction formula is as follows:
[0030] (3) Under nitrogen atmosphere, add 20 mmol of vinyl naphthyl organosilicon polyamine monomer and 270 mL of N,N-dimethylformamide to the reaction flask, stir evenly, add 90 mmol of 16-bromohexadecanoic acid and 104 mmol of triethylamine, react at 70°C for 15 h, extract with ethyl acetate and deionized water, concentrate the organic phase, separate by column chromatography (silica gel, 10% methanol in dichloromethane), and obtain vinyl naphthalene organosilicon monomer. The preparation reaction formula is as follows:
[0031] (4) Under nitrogen atmosphere, 65 g acrylamide, 12 g N,N-dimethylacrylamide, 5 g polyethylene glycol monomethyl ether acrylate and 2 g alkenylnaphthalene organosilicon monomer were dissolved in deionized water, the pH was adjusted to 7 with a 30% by mass sodium hydroxide aqueous solution, nitrogen was introduced, the mixture was heated to 70°C, 0.6 g ammonium persulfate was added dropwise, the reaction was continued for 4 h, and the mixture was naturally cooled to room temperature to obtain a temperature-resistant oil well cement fluid loss reducer.
[0032] Example 2 (1) Under nitrogen atmosphere, 80 mmol of methylvinyldichlorosilane and 240 mL of toluene were added to a reaction flask. After stirring, 164 mmol of 6-hydroxy-2-naphthaldehyde and 184 mmol of sodium hydride were added. The mixture was reacted at 110° C. for 5 h. The mixture was filtered, and the organic layer was washed with saturated brine. The mixture was separated by column chromatography (silica gel, 20% ethyl acetate in n-heptane). After drying, the vinylnaphthyl organosilicon dialdehyde monomer was obtained.
[0033] (2) Under nitrogen atmosphere, 147 mmol of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt and 420 mL of methanol were added to a reaction flask. After stirring evenly, 70 mmol of vinyl naphthyl organosilicon dialdehyde monomer was added. The mixture was stirred at 35°C for 2 h. Then, 175 mmol of sodium cyanoborohydride was added. The mixture was reacted at room temperature for 18 h. The mixture was filtered, concentrated under reduced pressure, separated by column chromatography (silica gel, 5% methanol in dichloromethane), and dried to obtain vinyl naphthyl organosilicon polyamine monomer.
[0034] (3) Under nitrogen atmosphere, 60 mmol of vinylnaphthyl organosilicon polyamine monomer and 720 mL of N,N-dimethylformamide were added to the reaction flask. After stirring evenly, 252 mmol of 16-bromohexadecanoic acid and 270 mmol of triethylamine were added. The mixture was reacted at 80 °C for 124 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated and separated by column chromatography (silica gel, 10% methanol in dichloromethane) to obtain vinylnaphthalene organosilicon monomer.
[0035] (4) Under nitrogen atmosphere, 60 g acrylamide, 10 g N,N-dimethylacrylamide, 6 g polyethylene glycol monomethyl ether acrylate and 4 g alkenylnaphthalene organosilicon monomer were dissolved in deionized water, the pH was adjusted to 6 with a 30% by mass sodium hydroxide aqueous solution, nitrogen was introduced, the mixture was heated to 80°C, 0.5 g benzoyl peroxide was added dropwise, the reaction was continued for 2 h, and the mixture was naturally cooled to room temperature to obtain a temperature-resistant oil well cement fluid loss reducer.
[0036] Example 3 (1) Under nitrogen atmosphere, 18 mmol of methylvinyldichlorosilane and 90 mL of toluene were added to a reaction flask. After stirring, 39.6 mmol of 6-hydroxy-2-naphthaldehyde and 45 mmol of sodium hydride were added. The mixture was reacted at 90° C. for 10 h. The mixture was filtered, and the organic layer was washed with saturated brine. The mixture was separated by column chromatography (silica gel, 20% ethyl acetate in n-heptane). After drying, the vinylnaphthyl organosilicon dialdehyde monomer was obtained.
[0037] (2) Under nitrogen atmosphere, 34.5 mmol of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt and 150 mL of methanol were added to the reaction flask. After stirring evenly, 15 mmol of vinyl naphthyl organosilicon dialdehyde monomer was added. The mixture was stirred at 20°C for 5 h. Then, 52.5 mmol of sodium cyanoborohydride was added. The mixture was reacted at room temperature for 18 h. The mixture was filtered, concentrated under reduced pressure, separated by column chromatography (silica gel, 5% methanol in dichloromethane), and dried to obtain vinyl naphthyl organosilicon polyamine monomer.
[0038] (3) Under nitrogen atmosphere, 12 mmol of vinylnaphthyl organosilicon polyamine monomer and 180 mL of N,N-dimethylformamide were added to the reaction flask. After stirring, 60 mmol of 16-bromohexadecanoic acid and 72 mmol of triethylamine were added. The mixture was reacted at 60 °C for 24 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated and separated by column chromatography (silica gel, 10% methanol in dichloromethane) to obtain vinylnaphthalene organosilicon monomer.
[0039] (4) Under nitrogen atmosphere, 58 g acrylamide, 12 g N,N-dimethylacrylamide, 7 g polyethylene glycol monomethyl ether acrylate and 6 g alkenylnaphthalene organosilicon monomer were dissolved in deionized water, the pH was adjusted to 8 with a 30% by mass sodium hydroxide aqueous solution, nitrogen was introduced, the mixture was heated to 60°C, 0.8 g azobisisobutyronitrile was added dropwise, the reaction was continued for 5 h, and the mixture was naturally cooled to room temperature to obtain a temperature-resistant oil well cement fluid loss reducer.
[0040] Example 4 (1) Under nitrogen atmosphere, 45 mmol of methylvinyldichlorosilane and 172 mL of toluene were added to a reaction flask. After stirring, 95.4 mmol of 6-hydroxy-2-naphthaldehyde and 106.5 mmol of sodium hydride were added. The mixture was reacted at 105° C. for 9 h. The mixture was filtered, and the organic layer was washed with saturated brine. The mixture was separated by column chromatography (silica gel, 20% ethyl acetate in n-heptane). After drying, the vinylnaphthyl organosilicon dialdehyde monomer was obtained.
[0041] (2) Under nitrogen atmosphere, 90 mmol of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt and 340 mL of methanol were added to a reaction flask. After stirring evenly, 40 mmol of vinyl naphthyl organosilicon dialdehyde monomer was added. The mixture was stirred at 30°C for 5 h. Then, 130 mmol of sodium cyanoborohydride was added. The mixture was reacted at room temperature for 16 h. The mixture was filtered, concentrated under reduced pressure, separated by column chromatography (silica gel, 5% methanol in dichloromethane), and dried to obtain vinyl naphthyl organosilicon polyamine monomer.
[0042] (3) Under nitrogen atmosphere, 35 mmol of vinyl naphthyl organosilicon polyamine monomer and 450 mL of N,N-dimethylformamide were added to the reaction flask. After stirring, 162 mmol of 16-bromohexadecanoic acid and 196 mmol of triethylamine were added. The mixture was reacted at 75 °C for 15 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated and separated by column chromatography (silica gel, 10% methanol in dichloromethane) to obtain vinyl naphthalene organosilicon monomer.
[0043] (4) Under nitrogen atmosphere, 55 g acrylamide, 14 g N,N-dimethylacrylamide, 8 g polyethylene glycol monomethyl ether acrylate and 8 g alkenylnaphthalene organosilicon monomer were dissolved in deionized water, the pH was adjusted to 7 with a 30% by mass sodium hydroxide aqueous solution, nitrogen was introduced, the mixture was heated to 65°C, 0.7 g ammonium persulfate was added dropwise, the reaction was continued for 4 h, and the mixture was naturally cooled to room temperature to obtain a temperature-resistant oil well cement fluid loss reducer.
[0044] Example 5 (1) Under nitrogen atmosphere, 25 mmol of methylvinyldichlorosilane and 120 mL of toluene were added to a reaction flask. After stirring, 53.5 mol of 6-hydroxy-2-naphthaldehyde and 60.5 mmol of sodium hydride were added. The mixture was reacted at 95° C. for 10 h. The mixture was filtered, and the organic layer was washed with saturated brine. The mixture was separated by column chromatography (silica gel, 20% ethyl acetate in n-heptane). After drying, the vinylnaphthyl organosilicon dialdehyde monomer was obtained.
[0045] (2) Under nitrogen atmosphere, 43 mmol of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt and 170 mL of methanol were added to a reaction flask. After stirring evenly, 20 mmol of vinyl naphthyl organosilicon dialdehyde monomer was added. The mixture was stirred at 30°C for 4 h. Then, 64 mmol of sodium cyanoborohydride was added. The mixture was reacted at room temperature for 18 h. The mixture was filtered, concentrated under reduced pressure, and separated by column chromatography (silica gel, 5% methanol in dichloromethane). After drying, the vinyl naphthyl organosilicon polyamine monomer was obtained.
[0046] (3) Under nitrogen atmosphere, 15 mmol of vinyl naphthyl organosilicon polyamine monomer and 210 mL of N,N-dimethylformamide were added to the reaction flask. After stirring, 69 mmol of 16-bromohexadecanoic acid and 78 mmol of triethylamine were added. The mixture was reacted at 80 °C for 24 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated and separated by column chromatography (silica gel, 10% methanol in dichloromethane) to obtain vinyl naphthalene organosilicon monomer.
[0047] (4) Under nitrogen atmosphere, 50 g acrylamide, 15 g N,N-dimethylacrylamide, 8 g polyethylene glycol monomethyl ether acrylate and 10 g alkenylnaphthalene organosilicon monomer were dissolved in deionized water, the pH was adjusted to 7 with a 30% by mass sodium hydroxide aqueous solution, nitrogen was introduced, the mixture was heated to 70°C, 0.6 g benzoyl peroxide was added dropwise, the reaction was continued for 3 h, and the mixture was naturally cooled to room temperature to obtain a temperature-resistant oil well cement fluid loss reducer.
[0048] Comparative Example 1 Under a nitrogen atmosphere, 65 g of acrylamide, 12 g of N,N-dimethylacrylamide, 5 g of polyethylene glycol monomethyl ether acrylate and 2 g of vinyl naphthyl organosilicon dialdehyde monomer (prepared in Example 1) were dissolved in deionized water, the pH was adjusted to 7 with a 30% by mass sodium hydroxide aqueous solution, nitrogen was introduced, heated to 70° C., 0.6 g of ammonium persulfate was added dropwise, the reaction was continued for 4 h, and naturally cooled to room temperature to obtain an oil well cement fluid loss reducer.
[0049] Comparative Example 2 Under a nitrogen atmosphere, 65 g of acrylamide, 12 g of N,N-dimethylacrylamide, 5 g of polyethylene glycol monomethyl ether acrylate and 2 g of vinyl naphthyl silicone polyamine monomer (prepared in Example 1) were dissolved in deionized water, the pH was adjusted to 7 with a 30% by mass sodium hydroxide aqueous solution, nitrogen was introduced, heated to 70° C., 0.6 g of ammonium persulfate was added dropwise, the reaction was continued for 4 h, and naturally cooled to room temperature to obtain an oil well cement fluid loss reducer.
[0050] Comparative Example 3 Under a nitrogen atmosphere, 65 g of acrylamide, 12 g of N,N-dimethylacrylamide, and 5 g of polyethylene glycol monomethyl ether acrylate were dissolved in deionized water, the pH was adjusted to 7 with a 30% by mass sodium hydroxide aqueous solution, nitrogen was introduced, the mixture was heated to 70°C, 0.6 g of ammonium persulfate was added dropwise, the reaction was continued for 4 h, and the mixture was naturally cooled to room temperature to obtain an oil well cement fluid loss reducer.
[0051] Preparation of cement slurry: It is carried out in accordance with the provisions of the standard GB / T 19139-2012 "Test Methods for Oil Well Cement", and the formula is: Jiahua G-grade oil well cement + 3% fluid loss additive by mass + seawater (water-cement ratio is 0.44).
[0052] Temperature resistance test: Add the prepared cement slurry into the 500mL filter cylinder of the high temperature and high pressure water loss instrument and fill it with 22.6cm 2 In the filter, set the temperature to 100℃, 150℃ and 250℃ respectively, open the pressure reducing valve of the nitrogen bottle, apply 6.9Mpa pressure, slowly unscrew the top valve and bottom valve of the filter cylinder, and use a measuring cylinder to collect the filtrate within 30 minutes to obtain the API water loss within 30 minutes.
[0053] Table 1 High temperature resistance test
[0054] It can be seen from the test results in the above table that with the increase of temperature, the API water loss gradually increases, but the growth rate is not large; at the same temperature, with the increase of the content of alkenyl naphthalene organosilicon monomer, the water loss gradually decreases. When the addition amount of the fluid loss reducer is only 3%, the API water loss of the cement slurry at 250°C in Example 4 is only 52mL, indicating that the prepared fluid loss reducer has a good air filtration loss effect at a high temperature of 250°C. This is because, on the one hand, the naphthalene ring has a stable aromatic ring structure and is not easy to rotate. Its rigid structure can withstand high temperatures without deformation or decomposition, which helps the fluid loss reducer maintain its original performance and form at high temperatures and can significantly improve the thermal stability of the fluid loss reducer; Siloxane has high bond energy and excellent heat resistance, and can maintain stable chemical properties at high temperatures. At the same time, siloxane has the characteristic of not being wetted by water, which helps the fluid loss reducer reduce the influence of water molecules at high temperatures, so that it can still maintain stable performance in high temperature and high humidity environments. The two work synergistically to play a high temperature resistance role; on the other hand, the multiple carboxylic acid and sulfonic acid groups introduced in the fluid loss reducer, after dissolving in water, are ionized to generate anions such as sulfonate and carboxylate, which are adsorbed on cement particles through electrostatic action and promote the extension of the polymer chain of the fluid loss reducer. At high temperatures, the molecular chain does not break in alkaline cement slurry, the group does not fall off, and the high temperature resistance is excellent.
[0055] In addition, since seawater contains salt ions of various components, it has good fluid loss control performance even at high temperatures, indicating that the water loss reducer has good salt resistance. The comparative example and comparative example 2 contain naphthalene rings and siloxanes with good heat resistance and have good high temperature resistance; comparative example 3 does not contain any heat-resistant groups and has poor high temperature resistance.
[0056] Cement slurry fluidity retention test: According to the relevant provisions of the national standard SY / T 5504.2-2013, the fluidity of cement slurry and the fluidity retention at 30min and 60min are tested.
[0057] Cement slurry sedimentation stability test: The prepared cement slurry is cured at 60℃ for 20min, and the free particle of the cement slurry and the density difference between the upper and lower parts are measured to characterize the sedimentation stability of the cement slurry.
[0058] Table 2 Dispersion performance test
[0059] It can be seen from the test results in the above table that the fluid loss agent prepared by the present invention can maintain the fluidity stability of cement slurry for a long time, indicating that the slurry fluid loss agent can not only be quickly adsorbed on cement particles in the early stage of hydration, but also continue to play a role in the hydration process to prevent cement particles from excessively aggregating due to hydration reaction; generally speaking, the smaller the density difference between the upper and lower parts of the cement slurry and the less the free liquid content, the better the sedimentation stability of the cement slurry, that is, the more uniform the dispersion of cement particles in the cement slurry.
[0060] It can be seen from the test results in the above table that the fluid loss reducer prepared by the present invention has good dispersibility. This is because, on the one hand, the multiple carboxylic acid and sulfonic acid groups introduced in the fluid loss reducer are ionized to generate anions such as sulfonate and carboxylate after dissolving in water, which are adsorbed on cement particles through electrostatic action, block the pores of cement particles, make the cement filter cake dense and compact, enhance the binding force between the fluid loss reducer and cement particles, and prevent the agglomeration and sedimentation of cement particles, which helps to form a hydration layer through hydration. When the fluid loss reducer molecules are adsorbed on the surface of cement particles, these hydration layers can reduce the friction between cement particles and further promote the dispersion of cement slurry; on the other hand, the introduced polyethylene glycol alkyl and hexadecyl long side chain structures can form an effective steric hindrance in a relatively extended conformation to prevent flocculation and precipitation between cement particles, and form a protective layer of a certain thickness and effective steric hindrance on the surface of cement particles, thereby effectively preventing close contact and agglomeration of cement particles, so that cement is highly dispersed.
[0061] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a heat-resistant oil well cement fluid loss reducer, characterized in that: The preparation method is carried out according to the following steps: Step (1), under a nitrogen atmosphere, adding a vinyl naphthyl organosilicon polyamine monomer and N,N-dimethylformamide to a reaction flask, stirring evenly, adding 16-bromohexadecanoic acid and triethylamine, stirring for reaction, after the reaction is completed, extracting with ethyl acetate and deionized water, concentrating the organic phase, and separating by column chromatography to obtain an vinyl naphthalene organosilicon monomer; Step (2), under a nitrogen atmosphere, dissolving 50-65 parts by weight of acrylamide, 10-15 parts of N,N-dimethylacrylamide, 5-8 parts of polyethylene glycol monomethyl ether acrylate and 2-10 parts of alkenylnaphthalene organosilicon monomer in deionized water, adjusting the pH with an aqueous sodium hydroxide solution, introducing nitrogen, heating to 60-80° C., adding dropwise 0.5-0.8 parts of an initiator, continuing the reaction for 2-5 hours, and naturally cooling to room temperature to obtain a temperature-resistant oil well cement fluid loss reducer.
2. The method for preparing the heat-resistant oil well cement fluid loss reducer according to claim 1, characterized in that: In the step (1), the molar ratio of the vinyl naphthyl silicone polyamine monomer, 16-bromohexadecanoic acid and triethylamine is 1:4.2-5:4.5-6.
3. The method for preparing the heat-resistant oil well cement fluid loss reducer according to claim 1, characterized in that: In the step (1), the reaction temperature is 60-80°C and the reaction time is 12-24h.
4. The method for preparing the heat-resistant oil well cement fluid loss reducer according to claim 1, characterized in that: The initiator in step (2) is any one of ammonium persulfate, benzoyl peroxide or azobisisobutyronitrile.
5. The method for preparing the heat-resistant oil well cement fluid loss reducer according to claim 1, characterized in that: In the step (2), the pH is adjusted to 6-8.
6. The method for preparing the heat-resistant oil well cement fluid loss reducer according to claim 1, characterized in that: The method for preparing the vinyl naphthyl organosilicon polyamine monomer in step (1) is carried out according to the following steps: Step S1, under a nitrogen atmosphere, add methylvinyldichlorosilane and toluene to a reaction flask, stir evenly, add 6-hydroxy-2-naphthaldehyde and sodium hydride, stir to react, filter after the reaction is completed, wash the organic layer with saturated brine, separate by column chromatography, and dry to obtain a vinylnaphthyl organosilicon dialdehyde monomer; Step S2, under a nitrogen atmosphere, add 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt and methanol to a reaction flask, stir evenly, add vinylnaphthyl organosilicon dialdehyde monomer, stir at 20-35°C for 2-5h, then add sodium cyanoborohydride, react at room temperature for 12-18h, filter, concentrate under reduced pressure, separate by column chromatography, and dry to obtain vinylnaphthyl organosilicon polyamine monomer.
7. The method for preparing the heat-resistant oil well cement fluid loss reducer according to claim 6, characterized in that: In the step S1, the molar ratio of methylvinyldichlorosilane, 6-hydroxy-2-naphthaldehyde and sodium hydride is 1:2.05-2.2:2.3-2.
5.
8. The method for preparing the heat-resistant oil well cement fluid loss reducer according to claim 6, characterized in that: In step S1, the reaction temperature is 90-110° C. and the reaction time is 5-10 h.
9. The method for preparing the heat-resistant oil well cement fluid loss reducer according to claim 6, characterized in that: In step S2, the molar ratio of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt, vinylnaphthyl organosilicon dialdehyde monomer, and sodium cyanoborohydride is 2.1-2.3:1:2.5-3.
5.
10. A heat-resistant oil well cement fluid loss reducer, characterized in that: Obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Dispersion dehydration-reducing agent for oil field well cementation and its preparing method
CN100355854C
High-temperature-resistant dispersed fluid loss agent for oil well cement and preparation method thereof
CN102191027B
Dispersant used in polymer cement mortar for oil field cementing, and preparation method thereof
CN102225988A
Comb type structure amphiprotic ionic polymer filtrate reducer and preparation method thereof
CN108676129A
Polycyclic polymer tackifying filtrate reducer for temperature-resistant and salt-resistant drilling fluid as well as preparation method and application of polycyclic polymer tackifying filtrate reducer
CN118994498A